Atividades educativas e estresse de mães de prematuros após a alta hospitalar: ensaio clínico randomizado - Bugs, Bruna Maria (2016)
Life expectancy premature newborns hospitalized have been positively influenced by scientific and technological advances. However, a premature birth breaks the expectations built by the family about a perfect and healthy baby. Thus, having a premature baby is a stress factor to the parents during the hospitalization and at home, because they have the responsibility for the care of a child with many specifics. This research aims to evaluate the influences of educative activities in stress levels of preterm mothers after the hospital discharge. A quantitative study was developed, as a randomized clinical trial, registered under RBR-9yz2pb on Registro Brasileiro de Ensaios Clínicos (Rebec) in which mothers of preterm babies hospitalized in Neonatal Intensive Care Unit (NICU) or Intermediate Care Unit (ICU) were divided into two groups: intervention and control. The Intervention Group (IG) was composed by 15 mothers that participated in educative activities in order to prepare to the hospital discharge. The Control Group (CG) was composed by 27 mothers who received the standard discharge of the unit. Stress levels were assessed in both groups using stress measurement scales validated in Brazil and applied in two moments: between the first and second hospitalization week using Parental Stress Scale: Neonatal Intensive Care Unit and between the third and sixth month after discharge, during the return in the premature follow-up ambulatory , applying the Parenting Stress Index (PSI). The IG answered the PSS-NICU before participating in educative activities. Maternal knowledge was assessed by instrument that obtained reliability by Cronbach's alpha 0.9257. This evaluation happened with a pre-test, applied to the IG and CG during hospitalization and a post-test, applied to the IG after participation in the educative activity and to the CG up to three days after hospital discharge. IG and CG overall stress score assessed by PPS-NICU showed a statistically significant difference (p = 0.022), giving the similarity of the groups in this aspect. The percentile overall score of stress assessed by IEP was not significantly different in the groups (p = 0.115). The reduction of stress after discharge was 2,68 times greater in IG than CG. In the assessment of knowledge, the mothers of the IG hit 13% more questions in the post-test, whereas CG mothers hit 3 % more. Gestational age and birth weight baby influenced the acquisition of knowledge. In the evaluation of the intervention, all mothers said the activity helped them to answer doubts and to increase confidence in taking care of children at home. The educative activity allowed IG mothers did not have increased levels of stress after discharge, considering the greater severity of the babies, providing a balance between the IG and CG.